Conceiving Christian America : embryo adoption and reproductive politics - Cromer, Risa (New York University Press, 2023)
"An insider's look at a powerful social movement that aims to transform how we think about frozen human embryos, reproductive politics, and the future of the nation"-- Provided by publisher.
Keywords: Frozen human embryos -- Moral and ethical aspects.; Human reproductive technology -- Religious aspects -- Christianity.; Human embryo -- Transplantation -- Moral and ethical aspects.; Fertilization in vitro, Human.; Adoption -- Religious aspects -- Christianity.; Adoption -- Moral and ethical aspects.; Fertilization in Vitro; Embryons humains congelés -- Aspect moral.; Procréation médicalement assistée -- Aspect religieux -- Christianisme.; Embryon humain -- Transplantation -- Aspect moral.; Fécondation in vitro.; Adoption -- Aspect moral.; Adoption -- Aspect religieux -- Christianisme.; FAMILY & RELATIONSHIPS / Adoption & Fostering.; Adoption -- Religious aspects -- Christianity; Fertilization in vitro, Human; Frozen human embryos -- Moral and ethical aspects; Human embryo -- Transplantation -- Moral and ethical aspects; Human reproductive technology -- Religious aspects -- Christianity; Ethics & moral philosophy.; Society.; Bulletin Board System (BBS).; Christian Right.; Digital humanities.; Political activism.; Transgender history.; US politics.; Web history.; antiabortion activists.; antiabortion movement.; assisted reproductive technologies.; cloud storage.; content delivery networks.; discourse.; download speeds.; embryo adoption.; ethnographic methods.; feminist anthropology.; global media.; in vitro fertilization.; infrastructure.; legal scholars.; net neutrality.; personhood politics.; pro-life movement.; reproductive politics.; saviorism.; science and technology studies (STS).; white pro-life evangelicalism.; white saviorism.; Electronic books.